A pre-experimental study: Spelling bee game to elevate vocabulary mastery of Gen Z students - Mawar, Putri Bulan; Anggreni, Afrillia (Measurement In Educational Research, 2025)
Vocabulary is the most crucial component for EFL learners in learning English because it is a key to acquiring and improving language skills. Nevertheless, to master vocabulary, the EFL learners need great effort. Therefore, this study aims to identify the effectiveness of spelling bee games in boosting vocabulary mastery of Gen Z students. This study employed a pre-experimental design with one group pre-test and post-test. The sample consisted of 32 students from class VII G, a show was selected purposively. The data collection involved pre-test and post-test. The data were analyzed using a parametric test (paired-sample test) assisted by SPSS 26. The result of this study finds that the significance of 2-tailed is lower than (<) 0.05, which reveals that spelling bee as a conventional game is still statistically effective in elevating Gen Z’ English vocabulary. Thus, conventional games can still be maintained to teach Gen Z students vocabulary, especially in teaching form (spelling) and use (constructing sentences).